2020
DOI: 10.22267/rcia.203701.127
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of carbon capture in different soil uses

Abstract: Carbon sequestration by soils in different production systems contributes greatly to the reduction of greenhouse gases. The objective of this study was to quantify the carbon stored in four land uses at different soil depths. To this end, a 22 factorial experiment in complete randomized block design (CRBD) was carried out. The factor A: land uses (natural pastures, shelterbelts, fodder banks, and potato crop) and the factor B: two soil depths (30 and 60cm), with three replications.  . As a result, statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This study further found that weeks is the optimum pruning frequency for obtaining higher fodder and SOC in fodder banks in Uganda (Fungo et al 2020). Solarte-Guerrero et al (2020) reported that Acacia decurrens-based fodder bank at 1 m ×1 m stored the highest (97.89 Mg/ha) SOC (60 cm depth) as compared to natural pasture (57.23 Mg/ ha) in Colombia. Thus, integration of fast growing fodder trees and adoption of appropriate management practices can substantially elevate soil carbon sequestration of various cropping systems.…”
Section: Carbon Storage Potential Of Tree Fodder Bankssupporting
confidence: 55%
“…This study further found that weeks is the optimum pruning frequency for obtaining higher fodder and SOC in fodder banks in Uganda (Fungo et al 2020). Solarte-Guerrero et al (2020) reported that Acacia decurrens-based fodder bank at 1 m ×1 m stored the highest (97.89 Mg/ha) SOC (60 cm depth) as compared to natural pasture (57.23 Mg/ ha) in Colombia. Thus, integration of fast growing fodder trees and adoption of appropriate management practices can substantially elevate soil carbon sequestration of various cropping systems.…”
Section: Carbon Storage Potential Of Tree Fodder Bankssupporting
confidence: 55%